Promoting a New Narrative for Progress and Prosperity: Tapping the Potential of the Brazilian G20 Presidency - Engels, Markus; J. Snower, Dennis (CEBRI-Revista: Brazilian Journal of International Affairs, 2024)
Brazil can make history with its G20 Presidency. With the main priorities of the Presidency–promoting social inclusion and food security; the clean energy transition and sustainable development; and reform of global governance institutions–the country can tackle major global problems by recoupling economic progress with social and environmental prosperity. This way, Brazil can ensure that people worldwide enjoy economic sufficiency, social cohesion, individual empowerment, and environmental sustainability.